Lectin binding patterns in normal, dysplastic and helicobacter pylori infected gastric mucosa - Vernygorodskyi, S.; Shkolnikov, V.; Suhan, D. (Experimental Oncology, 2017)
Aim: To analyze the glycoprotein binding sites of the gastric mucosa and its secreted mucus using lectin histochemistry in patients with chronic non-atrophic gastritis (CNAG) associated or not-associated with Helicobacter pylori infection with or without dysplasia. Materials and Methods: In order to identify the areas with glycoconjugates expression in gastric mucosa, 6 lectins (Canavalia ensiformis agglutinin — Con A, Sambucus nigra agglutinin — SNA, wheat germ agglutinin — WGA, soybean agglutinin — SBA, Helix pomatia agglutinin — HPA, peanut agglutinin — PNA) were used. Carbohydrate determinants were visualized according to the lectin-peroxidase-diaminobenzidine staining protocol. Biopsy material was obtained and processed by conventional histological methods. The samples from 84 patients (54 with CNAG) with low (n = 34) and high grade (n = 20) dysplasia, 38 patients were H. pylori-infected and 26 patients — H. pylori-noninfected) were used. The comparison group included 30 persons with CNAG without dysplasia (16 patients H. pylori-infected and 14 — noninfected). Results: In comparison to normal gastric mucosa, a low affinity of Con A was shown in 80% of patients with non-infected CNAG and 90% of H. pylori associated CNAG. In 70% of H. pylori-infected patients with CNAG and low grade dysplasia there was an increase of SNA expression compared with noninfected patients (p < 0.05). Regarding SBA labeling no differences were detected in the studied groups (p < 0.05). In H. pylori infected patients with CNAG and low grade dysplasia, WGA, HPA and PNA showed a strong reactivity with the gastric mucosa cells in 80; 75%, and 60% of patients, respectively. Conclusion: We suggest that a set of lectins in reaction with gastric epithelial and glandular cells can be used as a tool to obtain information about the dysplastic changes of the gastric mucosa and may offer new insight into gastric carcinogenesis and precancerous lesions treatment.